PENGARUH BERMAIN LEMPAR TANGKAP BOLA TERHADAP PERKEMBANGAN MOTORIK KASAR ANAK KELOMPOK A TK MUSLIMAT TUNAS HARAPAN MOJOAGUNG JOMBANG - Aziz, Aditya Nuraminudin; Puspita, Sylvie; Saadah, Firda Mila Turah Manur (LPPM STIKES HUSADA JOMBANG, 2025)
Background: Gross motor development encompasses the ability to execute bodily movements involving the contraction of large muscle groups in children. The proficient development of these skills can be facilitated through consistent stimulation, with activities such as playing throw-and-catch ball serving as a notable example. Objectives: This study aimed to determine the effect of engaging in throw-and-catch ball activities on the gross motor development of Group A children at Muslimat Tunas Harapan Kindergarten in Mojoagung, Jombang. Methods: Employing a pre-experimental design, this research utilized a one-group pretest-posttest approach with a total sampling technique. Consequently, a sample of 22 children from Group A at Muslimat Tunas Harapan Kindergarten in Mojoagung, Jombang, was included in the study. Results: The results indicated that before the intervention (ball throwing therapy), 2 respondents (9.1%) exhibited gross motor skills in the BSB (Berkembang Sangat Baik - Very Well Developed) category. Following the intervention, a significant improvement was observed, with 10 respondents (45.5%) achieving the BSB category in gross motor skills. Furthermore, the Wilcoxon test yielded an Asymptotic Significance (2-tailed) value of 0.001, which is less than the alpha level of 0.05 (p<0.05). This outcome led to the rejection of the null hypothesis (Ho) and the acceptance of the alternative hypothesis (H1), confirming a statistically significant influence of playing throw and catch ball on the gross motor development of Group A children at Muslimat Tunas Harapan Kindergarten, Mojoagung, Jombang. Conclusion: Stimulating children's gross motor skills from an early age is crucial, as it enhances their physical movements essential for subsequent growth. It is anticipated that implementing ball-throwing games can serve as a viable alternative therapy for promoting gross motor development in children.